Data journalism practices during COVID‑19 in the main Spanish newspapers: Features of data‑driven stories and the influence of the pandemic on newsrooms. - Córdoba-Cabús, Alba; Farias-Batllé, Pedro (Routdledge, 2024)
This chapter examines data journalism stories published in El País and El Mundo (N= 287). Through content analysis, the aim is to evaluate the importance given to stories about the coronavirus and to identify the characteristics of both the narrative and visual parts of the articles. In addition, focussed interviews were conducted with the data teams to delve deeper into the organisational structure and understand how the pandemic has influenced the production process. Amongst others, the results show significant differences in the practice of data journalism. El País publishes more in-depth stories with analysis and background, and more often achieves the optimum degree of transparency. In turn, data journalism at El Mundo seems to be relegated to the background. However, both teams agree that the coronavirus has transformed their routines, shortening the production process, and that the time limitation was compounded by the extreme disparity amongst the numbers and formats provided by the public administrations. El Mundo has an additional obstacle: it only has one person on staff dedicated to data, while the data team at El País has three staff members, which makes it impossible for El Mundo to go too deeply into the data.
Política de acceso abierto tomada de:https://www.routledge.com/our-products/open-access-books/publishing-oa-books/chapters
Uno de los autores, mediante conversación telefónica, dice tener permiso de Routledge para depositar en abierto el preprint del capítulo de libro (16/01/2025)
Keywords: Periodismo - Proceso de datos; Data Journalism; Spanish Newspapers; COVID-19; Newspaper content analysis; Journalism practices